A Brief Analysis of an Integrated Fish-Plant System through Phase Planes. Issue 13 (2018) - Carlos-Hernandez, Salvador; Diaz-Jimenez, Lourdes
Abstract: This paper focuses on the integration of two processes (aquaculture and hydroponics) into a single aquaponics system to promote a mutualist relationship between fishes and vegetables. After the description of the two sub-models, they are combined as a mutualist system considering bidirectional and facultative relationships between fishes and plants. Recirculation of nutrients is represented by recirculation coefficients. Positive and negative effects of the interaction are considered in the mutualist model. The integrated model is simulated considering different operation conditions and analyzed though phase planes. The obtained results show that recirculation of nutrients improve the increase of weight on fishes: it is possible to triplicate the initial weight. On the other side, vegetables do not show remarkable benefits which is likely due to the model structure.